FENOMENA BERDUAAN DENGAN TUNANGAN (ANALISIS FATWA SYEKH YUSUF AL-QARADHAWI) - Nurfazila,; Azwar, Zainal (An-Natiq Jurnal Kajian Islam Interdisipliner, 2024)
Traveling alone without being accompanied by a mahram between two people who are engaged is considered normal for some people in Indonesia, and it is not uncommon for people to fall into adultery. In fact, this is prohibited in Islam. This article aims to analyze the ijtihad method used by Yusuf al-Qaradawi regarding the prohibition of being alone with his fiancee. This research is library research with a fiqh proposal approach. Data was collected from books and other scientific works that are relevant to this study. The collected data is analyzed using content analysis, namely research that is an in-depth discussion of the content of written or printed information and then concludes based on the data collected and analyzed. The result of this research is that Yususf al-Qaradawi issued a fatwa regarding the prohibition of being alone with a fiancé using the ijtihad Qiyas method, where he stated that having seclusion between a man and a woman who is engaged is the same as bringing yourself closer to the act of adultery. For the reason that even though various ceremonies are carried out to celebrate the engagement, this is nothing more than just to strengthen and solidify it. And the Khitbah, no matter what the circumstances, will not be able to give any rights to the suitor but can only prevent other men from proposing to her.